605 Group and Save Sampling in Total Knee and Hip Arthroplasty: Is It Necessary?. (12th October 2021) - Mepani, V; Raheman, F; Nasr, P
Abstract: Aim: To induce a change in practice with regard to pre-op G&S sampling. This is common practice in elective orthopaedics. Transfusion rates are negligible. Therefore, omitting this practice can reduce the financial burden on the Trust. Method: Patient's undergoing elective primary total knee or hip arthroplasty over a 1-year period were retrieved from a database. Data regarding pre/post-op haemoglobin levels and transfusion status was obtained from patient case notes and Trust ICE pathology reporting system. Results: There were a total of 454 patient's (251 undergoing TKR, 203 undergoing THR). Four patient's (1.6%) in the TKR group and 11 patient's (5.4%) in the THR group required transfusion. Of these patient's, 5 had cardiac problems and 6 had pre-operative anaemia. Conclusions: Routine G&S sampling is unnecessary in the majority of cases and should only be reserved for certain cases (patient's with significant cardiac problems and those with a transfusion history). Patient's with pre-operative anaemia should have optimisation of haemoglobin level prior to the procedure.